ONE-YEAR AUDIT OF PATIENTS ADMITTED WITH THYROID DISORDERS TO THE MEDICAL DEPARTMENT, SIBU HOSPITAL - Ying, Lau Pei; Xian, Lai Shu; Chwen, Eunice Lau Yi (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The prevalence of thyroid disorders in Malaysia is around 3.4%. It is the second most common endocrine disorder after diabetes. Organ dysfunction related to thyroid disorders such as hyperthyroidism and hypothyroidism may result in significant morbidity and mortality. METHODOLOGY This was a retrospective review of patient medical records who were admitted to the medical department of Hospital Sibu between January 2022 to December 2022 department with hyperthyroidism and hypothyroidism. Patient demographics, clinical and biochemical data were documented and analysed RESULT There was a total of 94 admissions during this period. The mean patient age was 57.2 years (14 to 91 years old) with a female preponderance (61%). Most of the patients were thyrotoxic, 64% while 36% had hypothyroidism. The most common indication for hospitalization was atrial fibrillation (AF) (33%). Cardiac disease was a complication in 52% of admissions, predominantly AF and heart failure. Other thyroid-related complications included stroke, hyponatremia, hypokalaemic periodic paralysis and agranulocytosis. 2 (2%) patients were admitted for thyroid storm. Approximately one-third of patients were newly diagnosed during the admission and 5 (5%) patients had previously defaulted follow-up and treatment. CONCLUSION This study shows that a large proportion of patients admitted had poorly controlled thyroid function with multiple complications. This highlights the need for improved education and access to diagnostic and treatment facilities in our local population.